Enhancing Blood Outgrowth Endothelial Cells for Optimal Coating of Blood Contacting Surfaces - Yuan, Yifan (Université d'Ottawa / University of Ottawa, 2017)
Implantable cardiovascular biomaterials have been widely applied in multiple cardiovascular disorders such as coronary artery disease, heart failure, and abdominal aortic aneurysms. However the failure modes of cardiovascular biomaterials are not uncommon, which is mainly due to the complications on blood-contacting surfaces such as thrombosis, calcification, and inflammation. Endothelium locates the inner surface of vessel lumen and is a critical regulator of vascular homeostasis. However, a readily available functional autologous source of endothelium has been hard to achieve. Human blood outgrowth endothelial cells (BOECs), cultured from peripheral blood mononuclear cells are proliferative and express endothelial protein profiles and as such are a very promising novel cell source for cardiovascular biomaterials coating. Endothelial nitric oxide synthase (eNOS) is an important regulator of vascular homeostasis and loss of eNOS activity is a hallmark of endothelial dysfunction. My data demonstrated that BOECs express markedly lower eNOS protein, mRNA as well as activity levels when compared to mature endothelial cells (ECs). My first project was to use transient transfection methods along with minicircle DNA to enhance eNOS expression levels in BOECs. Two promoters were tested in BOECs, the CMV promoter (pMini-CMV-eNOS) and the EF1α promoter (pMini-EF1α-eNOS). Transfection with pMini-CMV-eNOS achieved 24.8 ± 5.1 times more eNOS expression when compared to null transfected cells at 24 hours, a marked improvement over that achieved with conventional PVAX plasmid (10.2 ± 4.7 fold increase) or pMini-EF1α-eNOS (8.2 ± 1.2 fold increase both compared to null transfected control). pMini-CMV-eNOS mediated overexpression improved cell migration and network formation. When cultured on Osteopontin (OPN) coated surfaces, transient transfection with plasmid eNOS in BOECs can markedly enhance cell spreading and adhesion to ECM modified surfaces. These results suggest that eNOS expression in BOECs is suboptimal and BOECs may be functionally improved by techniques to enhance expression of this critical homeostatic regulator. Extracellular matrix (ECM) proteins have been shown to negatively regulate eNOS expression and NO production in mature ECs. In addition, the deposition of Col IV and Col I in BOECs is higher compared to that in mature ECs. Thus, I have proposed that the lower eNOS expression/activity in BOECs compared to mature ECs is due to higher ECM deposition. When grown on fibronectin, type I collagen, type IV collagen and laminin, significantly decreased eNOS protein in HUVECs were found compared to cells on polystyrene. Interestingly, when cultured on polystyrene, BOECs express significantly more extracellular matrix (ECM) proteins especially type I collagen compared to mature ECs. Blocking collagen synthesis significantly enhanced eNOS expression in BOECs (1.77 ± 0.41 fold increase). My results suggest that the regulation of eNOS in BOECs and mature ECs is similar and the reduced eNOS level in BOECs may be due to their increased collagen production. ECM proteins regulate intracellular signaling transduction primarily through integrin signaling associated with focal adhesion complexes. I have proposed that ECM proteins regulation on eNOS signaling in BOECs and mature ECs is through integrin and integrin-associated proteins. Matrix mediated eNOS downregulation was blocked by β1 integrin siRNA and focal adhesion kinase siRNA transfection in both BOECs and HUVECs. In addition, inhibitors of actin polymerization (e.g. ROCK inhibitors and cytochalasin D) block the effect of ECM on eNOS signaling. Taken together, my results suggest that ECM proteins regulate eNOS expression via a β1 integrin/FAK/actin polymerization dependent mechanism.
Keywords: BOECs; ECM; eNOS; Blood contacting surface